Selection of promising apple genotypes for columnar growth habit and scab resistance using diagnostic DNA markers - N. I. Savel’ev; A. S. Lyzhin; N. N. Savel’eva (Вавиловский журнал генетики и селекции, 2016)
Monogenic scab resistance and columnar growth habit are important breeding traits of apple. The use of molecular markers very accurately determines the presence of necessary genes in the genome early during ontogenesis and reduces the time of selection. The purpose of this study was molecular genetic testing of initial forms of apple and hybrid seedlings of apple to identify carriers of the target alleles of genes for monogenic scab resistance (Rvi6) and columnar growth habit (Co) and the clarification of the pattern of inheritance of the Co and Rvi6 genes in hybrid progeny populations. This paper presents the results of molecular genetic analysis of varieties Valuta, Uspenskoe, Belarusskoe sladkoe and seedlings of the Valuta×Uspenskoe and Valuta×Belarusskoe sladkoe hybrid families for genes controlling columnar growth habit (Co) and scab resistance (Rvi6). The presence of the dominant allele of the Co gene was diagnosed with primers 29f1 and JWI1r flanking the 5’-end of the insert at the Co locus controlling columnar genotypes. Allelic status of the Rvi6 gene was determined with the AL07-SCAR marker mapping at about 0.2 cM from the Rvi6 locus. The correlation frequency of inheritance of the allelic states of these genes has been determined. Valuta×Uspenskoe crosse yielded 48.1 % columnar genotypes and 77.8 % scab-immune genotypes; Valuta×Belarusskoe sladkoe crosses, 46.8 % and 68.0 %, respectively. The observed segregation conforms to the expected Mendelian ratios: 1:1 for columnar habit and 3:1 for scab resistance. The joint inheritance of columnar growth habit and monogenic resistance to scab has been analyzed. The hybrid seedlings that had the dominant Co allele together with the Rvi6 gene in the homozygous dominant state (Rvi6 Rvi6) in their genome have been identified, which can significantly intensify the selection process and run it into 100 % of hybrid seedlings with monogenic scab resistance and up to 50 % of genotypes with columnar growth habit.